Stabilization of a Fixed Speed IG Based Wind Farm using Variable Speed PMSG - Tasneem, Zinat; Sheikh, M.R.I. (Rajshahi University Journal of Science and Engineering, 2015)
To optimize the output power and reduce the frequency fluctuation in conventional fixed speed Induction Generator (IG) based wind farm, various controlling devices are used. But, this paper proposes that Permanent Magnet Synchronous Generator (PMSG) can work both as a power producing device and as a controlling device for IG. In this paper a more practical case has been considered where a wind farm is operated with a set of Synchronous Generators (SG). Thermal, Hydro and Nuclear Governors have been used for SGs. Wind farm has a capacity of 20% of the total SGs capacity. Both two-level and three-level converter-inverter based PMSG have been considered. Comparative results between IG and IG with PMSG are shown. Simulation results prove the effectiveness of the proposed system. Simulations have been carried out by using the laboratory standard power system software package, PSCAD/EMTDC.